Anesthetic Management of a Patient with Sustained Severe Metabolic Alkalosis and Electrolyte Abnormalities Caused by Ingestion of Baking Soda - Jose Soliz; Jeffrey Lim; Gang Zheng (Case Reports in Anesthesiology)
The use of alternative medicine is prevalent worldwide. However, its effect on intraoperative anesthetic care is underreported. We report the anesthetic management of a patient who underwent an extensive head and neck cancer surgery and presented with a severe intraoperative metabolic alkalosis from the long term ingestion of baking soda and other herbal remedies.